Metabolic Enzymes Enjoying New Partnerships as RNA-Binding Proteins. (December 2015) - Castello, Alfredo; Hentze, Matthias W.; Preiss, Thomas
Abstract : In the past century, few areas of biology advanced as much as our understanding of the pathways of intermediary metabolism. Initially considered unimportant in terms of gene regulation, crucial cellular fate changes, cell differentiation, or malignant transformation are now known to involve 'metabolic remodeling' with profound changes in the expression of many metabolic enzyme genes. This review focuses on the recent identification of RNA-binding activity of numerous metabolic enzymes. We discuss possible roles of this unexpected second activity in feedback gene regulation ('moonlighting') and/or in the control of enzymatic function. We also consider how metabolism-driven post-translational modifications could regulate enzyme–RNA interactions. Thus, RNA emerges as a new partner of metabolic enzymes with far-reaching possible consequences to be unraveled in the future. Trends: Genetic control of metabolism is currently best understood at the level of transcription and epigenetics. Only limited information is available on post-transcriptional regulation of metabolism. While a few metabolic enzymes were previously known to moonlight as RNA-binding proteins in physiologically relevant contexts, recent discoveries highlight that several dozen of metabolic enzymes belonging to a wide spectrum of pathways exhibit RNA-binding activity in living mammalian cells. Abundant RNA–enzyme interactions might suggest novel roles of RNA in affecting enzyme function, for instance, as competitive inhibitors or allosteric regulators. A function of RNA as assembly scaffold for enzyme complexes is also conceivable, with potentially wide-ranging implications for our understanding of how cells organize and control metabolic flux. Finally, enzymes can moonlight as regulators of (m)RNAs, as exemplified by aconitase/IRP1 and GAPDH.